2013
DOI: 10.26530/oapen_627772
|View full text |Cite
|
Sign up to set email alerts
|

Borders and Border Regions in Europe : Changes, Challenges and Chances

Abstract: An electronic version of this book is freely available, thanks to the support of libraries working with Knowledge Unlatched. KU is a collaborative initiative designed to make high quality books Open Access for the public good. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDerivs 3.0 (BY-NC-ND). Creative Commons Attribution-NonCommercial-NoDerivs 3.0 (BY-NC-ND). which means that the text may be used for non-commercial purposes, provided credit is given to the author. For details g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Since 1990, the most important instrument for the implementation of the European Union's Cohesion Policy in border areas has undoubtedly been the European Cross Border Cooperation program (Interreg), which aims to encourage economic growth in border areas, having among its objectives the acceleration of regional development [49]. The program was created to stimulate cooperation between institutions and communities located on both sides of the border, through the development of crossborder socio-economic centers with common development strategies (Euroregions) [50][51][52]. Interregional cooperation projects are included in the first pillar of the Interreg program, which aims to improve the exchange of experience and the sharing of common practices, as well as the preparation of action plans for the integration and implementation of good practices within regional development policies [42].…”
Section: Introduction and Theoretic Backgroundmentioning
confidence: 99%
“…Since 1990, the most important instrument for the implementation of the European Union's Cohesion Policy in border areas has undoubtedly been the European Cross Border Cooperation program (Interreg), which aims to encourage economic growth in border areas, having among its objectives the acceleration of regional development [49]. The program was created to stimulate cooperation between institutions and communities located on both sides of the border, through the development of crossborder socio-economic centers with common development strategies (Euroregions) [50][51][52]. Interregional cooperation projects are included in the first pillar of the Interreg program, which aims to improve the exchange of experience and the sharing of common practices, as well as the preparation of action plans for the integration and implementation of good practices within regional development policies [42].…”
Section: Introduction and Theoretic Backgroundmentioning
confidence: 99%
“…Generally speaking, the range of about 50 km from the international boundary has obvious border characteristics [43]. In this study, a buffer zone of 50 km around China's land boundary is used as the study area (Figure 1), which is identified as China's border area in this paper.…”
Section: Study Areamentioning
confidence: 99%
“…In contrast, cultural and political differences, along with institutional systems, are able to transform borders into physical, social, cultural and mental barriers (Paasi and Prokkola, 2008; Mathä and Wintr, 2009; Cooper, 2015). Those differences and similarities may represent either an obstacle to cross‐border integrations or successful integration (Lundquist and Trippl, 2009; Decoville et al, 2013; Möller et al, 2018): according to Lechavalier and Wielgohs (2013), an extreme interpretation of the latter case could be Ohmae’s idea of “borderless world”, where state borders become meaningless (Ohmae, 1994).…”
Section: Introductionmentioning
confidence: 99%